CLASSIFICATION OF PRAGMATIC MEANING IN CONTEXT - Mirzayeva Nigorakhon Anvarovna, Ismailov Turgun Salakhiddinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article deals with the classification of pragmatic meaning in a certain context. In pragmatic meaning, words have meanings that go beyond their literal meaning. This study examines imitative meaning, opposite meaning, broadened or narrowed meaning, and distortional meaning as approaches to classifying pragmatic meaning, also the impact of context on pragmatic meaning, as well as the obstacles and limitations associated with defining such meaning. Through the investigation of examples in everyday language, we can gain a deeper understanding of how pragmatic meaning is constructed and interpreted across different contexts.